American raiders : the race to capture the Luftwaffe's secrets - Samuel, Wolfgang W. E. (University Press of Mississippi, 2004)
World War II ℗· Cold War-- & . At the close of World War II, Allied forces faced frightening new German secret weapons--buzz bombs, V-2s, and the first jet fighters. When Hitler's war machine began to collapse, the race was on to snatch these secrets before the Soviet Red Army found them. The last battle of World War II, then, was not for military victory but for the technology of the Third Reich. In American Raiders: The Race to Capture the Luftwaffe's Secrets Wolfgang Samuel assembles from official Air Force records and survivors' interviews the largely untold stories of the disarmament of the.